Future teachers’ training to application of cognitive barriers in professional activities during the Covid-19 pandemic - Glazkova, Iryna; Khatuntseva, Svitlana; Vaseiko, Yuliia; Shymanovych, Iryna; Yaroshchuk, Liliia (Amazonia Investiga, 2022)
New challenges for the education system have appeared due to the COVID-19 pandemic, that is why it is crucial to improve teachers’ training. There are instances that prevent the entire manifestation of the character, his/her self-achievement, self-expression, and self-agency. Such instances are barriers that accompany the educational procedure. The aim of the research is to give theoretical substantiation and offer pedagogical technology, which provides future teachers’ training on the application of cognitive barriers in their professional activities in terms of the pandemic caused by COVID-19. The main hypothesis of the research is the idea that specially organized future teachers’ training focusing on the formation of their competence in the application of cognitive barriers is the basis of their successful professional activities. The research methodology is built on the dialectical unity of such methods: comparative historical method, genetic method, competence-based method, systemic method, synergetic method. The proposed technology is built on the general didactic and specific principles and is accomplished via motivational, procedural, stages of obtaining experience, analytical, and reflexive stages involving appropriate strategies and tactics. It provides the result in the formation of future teachers’ competence in the application of cognitive barriers in professional activities.
Keywords: teachers’ training; cognitive barriers; professional activity; educational process; the COVID-19 pandemic